Analisis Penagihan Pajak Terhadap Pencairan Tunggakan Pajak Penghasilan Wajib Pajak Orang Pribadi Pada KPP Pratama Demak Tahun 2023 - sumbodo, eka kusuma; Safitri, Julia; Rahayu, Heffi Christya (Fakultas Ekonomi dan Bisnis Universitas Pekalongan, 2024)
The purpose of this study is to determine the effect of tax collection on the disbursement of income tax arrears of individual taxpayers at Kantor Pelayanan Pajak Demak. The research method used in this thesis research is to use descriptive statistical data analysis, namely research testing with the SPSS 22.0 application and calculating the percentage of the tax disbursement process at Kantor Pelayanan Pajak Demak. The research results from this thesis are that tax collection actions using Warning Letters, Force Letters , Confiscation Orders issued at KPP Pratama Demak have an influence on tax disbursement and the tax income